A preliminary study of the need of medical care facilities for older people among local authority areas / Muhamad Asri Abdullah Kamar - Abdullah Kamar, Muhamad Asri (Universiti Teknologi Mara Cawangan Pulau Pinang, 2019)
The topic of medical care facilities for older people is fast becoming a challenge in an aging society such as Malaysia. The objective of this preliminary study is to examine the need for medical care facilities for older people among the local authority areas in Malaysia. The older people have been the focus of this study because they need more medical care than young people. This paper utilized the data available from the Department of Statistics, Malaysia. Overall, this study indicates that the number of older people differs obviously among the local authority areas in Malaysia. Bigger local authority areas of major towns have a higher number of older people. The top five local authority areas involved are located at Kuala Lumpur, Pulau Pinang, Ipoh, Seberang Perai and Petaling Jaya. Instead, smaller local authority areas (unless Municipal Council of Pasir Gudang and Corporation of Putrajaya) have a lower number of older people groups. Other local authority areas are located at Pengkalan Hulu, Nabawan, and Cameron Highlands. The findings suggest that local governments, especially of major towns, should have proper planning of suitable medical care facilities for older people.